Shallow Subsurface Layer Assessment Using 2-D Resistivity Imaging And Ground Penetrating Radar (Gpr) At Coastal Area Of Penang Island: Case Study At Minden, Teluk Kumbar And Balik Pulau - Yusof, Azim Hilmy Mohamad (2018)
Investigation about the shallow subsurface layer is widely conducted in the geophysics world. Every researcher used different methods to investigate the subsurface layer depending on the situation that they were in. For this research, 2-D resistivity imaging and GPR method were used to investigate the shallow subsurface layer at the coastal area. Soil analysis at each of the study area was also conducted to enhance the accuracy of the acquired data. The main objective of this research is to characterise shallow subsurface layer in coastal area using geophysical method at Teluk Kumbar, USM Minden and Balik Pulau.